SMART LABORATORY MANAGEMENT: DIGITAL TECHNOLOGY INTEGRATION FOR 21ST-CENTURY SCIENCE LEARNING - Hartati Hartati; Nurdin Nurdin; Mohammad Djamil M. Nur (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
The advancement of digital technology is driving the transformation of science laboratory management toward a more modern, effective, and adaptive system aligned with the demands of 21st-century learning. This study aims to describe the implementation of digital technology-based Smart Laboratory Management in supporting science learning oriented toward 21st-century skills. The novelty of this study lies in its integrated analysis of Smart Laboratory Management implementation as a unified system that simultaneously integrates digital laboratory governance and the development of students' 21st-century skills, particularly within the context of madrasas and secondary schools in Indonesia a perspective that has not been comprehensively examined in prior research. The study employed a qualitative approach using a case study design. The research was conducted at science laboratories in madrasas and secondary schools. Data were collected through observation, in-depth interviews, and documentation. Research informants consisted of laboratory heads, science teachers, laboratory technicians, and students. Data analysis followed the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that Smart Laboratory Management was implemented through the digitalization of laboratory administration, the use of inventory barcodes, the utilization of equipment and materials management applications, and the integration of digital learning media into practicum activities. This system was capable of enhancing laboratory management effectiveness, accelerating access to inventory information, improving students' collaboration skills and digital literacy, and supporting 21st-century skills-based science learning. Implementation challenges included limitations in technological infrastructure, the digital competence of laboratory staff, and budget constraints for system development. This study implies that digital technology-based laboratory transformation is an essential requirement for improving the quality of modern science learning. ABSTRAK Perkembangan teknologi digital mendorong transformasi pengelolaan laboratorium IPA menuju sistem yang lebih modern, efektif, dan adaptif terhadap kebutuhan pembelajaran abad 21. Penelitian ini bertujuan untuk mendeskripsikan implementasi Smart Laboratory Management berbasis teknologi digital dalam mendukung pembelajaran IPA yang berorientasi pada keterampilan abad 21. Kebaruan penelitian ini terletak pada kajian terpadu yang menganalisis implementasi Smart Laboratory Management sebagai sistem tunggal yang secara simultan mengintegrasikan tata kelola laboratorium digital dan pengembangan keterampilan abad 21 peserta didik, khususnya dalam konteks madrasah dan sekolah menengah di Indonesia suatu perspektif yang belum secara komprehensif dikaji dalam penelitian sebelumnya. Penelitian menggunakan pendekatan kualitatif dengan jenis studi kasus. Lokasi penelitian dilakukan pada laboratorium IPA di tingkat madrasah/sekolah menengah. Teknik pengumpulan data dilakukan melalui observasi, wawancara mendalam, dan dokumentasi. Informan penelitian terdiri atas kepala laboratorium, guru IPA, laboran, dan peserta didik. Analisis data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa implementasi Smart Laboratory Management dilakukan melalui digitalisasi administrasi laboratorium, penggunaan barcode inventaris, pemanfaatan aplikasi pengelolaan alat dan bahan, serta integrasi media pembelajaran digital dalam kegiatan praktikum. Sistem ini mampu meningkatkan efektivitas pengelolaan laboratorium, mempercepat akses informasi inventaris, meningkatkan keterampilan kolaborasi dan literasi digital peserta didik, serta mendukung pembelajaran IPA berbasis keterampilan abad 21. Kendala implementasi meliputi keterbatasan infrastruktur teknologi, kompetensi digital tenaga laboratorium, dan keterbatasan anggaran pengembangan sistem. Penelitian ini memberikan implikasi bahwa transformasi laboratorium berbasis teknologi digital menjadi kebutuhan penting dalam meningkatkan mutu pembelajaran IPA modern.